2008
DOI: 10.1089/gte.2007.0120
|View full text |Cite
|
Sign up to set email alerts
|

VNTR Polymorphism of the DRD4 Locus in Different Pakistani Ethnic Groups

Abstract: The present study was designed to investigate the dopamine receptor D4 (DRD4) locus variable number of tandem repeat (VNTR) allelic distribution in different Pakistani ethnic groups. DNA samples from nine different ethnic groups of Pakistan were analyzed. Greek and Somali samples were included as representatives of the European and African populations, respectively. Pakistani, Greek, and Somali populations were also compared to the published data on different world populations. The allelic distribution reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Sindhi, a population of mixed origin, Baluch claiming Syrian origin, and Brahui claiming Dravidian origin all showed allelic frequencies closer to each other supporting our previous conclusion (Ayub et al, 2003;Quintana-Murci et al, 2004). Lower frequency of T allele in Mohanna and Makrani Negroid also explains their relatedness to African population (Qamar et al, 1999;Mansoor et al, 2008).…”
Section: C677t Polymorphism Among Pakistani Ethnic Groups 523supporting
confidence: 78%
See 1 more Smart Citation
“…Sindhi, a population of mixed origin, Baluch claiming Syrian origin, and Brahui claiming Dravidian origin all showed allelic frequencies closer to each other supporting our previous conclusion (Ayub et al, 2003;Quintana-Murci et al, 2004). Lower frequency of T allele in Mohanna and Makrani Negroid also explains their relatedness to African population (Qamar et al, 1999;Mansoor et al, 2008).…”
Section: C677t Polymorphism Among Pakistani Ethnic Groups 523supporting
confidence: 78%
“…Our laboratory has remained involved in determining the genetic relationship of various ethnic groups as well as genetic predisposition to various ailments. In continuation of our interest, the present study describes the prevalence of this polymorphism in Pakistan and also reports the importance of MTHFR C677T in predicting genetic relatedness of various ethnic groups and a comparison with previously described genetic markers from our group (Qamar et al, 2002;Quintana-Murci et al, 2004., Mansoor et al, 2008. These data are of considerable significance from a public health perspective and will facilitate predicting population-based risk factors for a number of congenital and other anomalies associated with MTHFR polymorphisms in Pakistan.…”
Section: Introductionmentioning
confidence: 76%
“…For example, the frequencies of short alleles are 89.7% among Vietnamese (Vietnam), 55.2% for Kazakhs from the east Ural, 36.0% for Bashkirs from the east Ural, and 18.3% for Bashkirs from the west Ural, but 8.5% for Russians from Northwest region of the Russian Federation [39]. Ethnic differences were described for other minisatellite repeats [40][41][42][43]. Thus, this feature of UPS29 must be considered when conducting "case-control" studies.…”
Section: Introductionmentioning
confidence: 99%
“…In a study in 2008 in Pakistan which was conducted on 474 volunteers, it was shown that the most common allele in the Persian breed is allele 4 repeat with frequency of 70.1%. 18 Allele7 repeat in the Persians group was obtained as 8.5% that was second after allele4. Fig.…”
Section: Discussionmentioning
confidence: 95%